2004
DOI: 10.1007/s00464-003-8827-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy for pheochromocytoma

Abstract: Despite concern about increased operative times and morbidity associated with pheochromocytoma, our experience supports that laparoscopic adrenalectomy may be performed as safely as, and achieve outcomes similar to, those for other diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(23 citation statements)
references
References 21 publications
1
20
1
1
Order By: Relevance
“…Th ey concluded that LA for PHEO, including large tumors, is safe, feasible, and eff ective with appropriate perioperative hemodynamic control (Hirayama et al 2015). Th e same was concluded by other authors (Jaroszewski et al 2003;Cheah et al 2002;Kalady et al 2004;Kercher et al 2005;Mezzadri et al 2010;Sommerey et al 2015).…”
Section: Surgery Of Pheochromocytomasupporting
confidence: 77%
“…Th ey concluded that LA for PHEO, including large tumors, is safe, feasible, and eff ective with appropriate perioperative hemodynamic control (Hirayama et al 2015). Th e same was concluded by other authors (Jaroszewski et al 2003;Cheah et al 2002;Kalady et al 2004;Kercher et al 2005;Mezzadri et al 2010;Sommerey et al 2015).…”
Section: Surgery Of Pheochromocytomasupporting
confidence: 77%
“…Blood loss also is reported to be higher with PHE [16,17]. Furthermore, there is variability in the reported morbidity for LA, with higher complication rates reported for PHE patients than for non-PHE patients [8,19].…”
Section: Discussionmentioning
confidence: 78%
“…Most reports indicate that the tumor size for a PHE is significantly larger than for a non-PHE [15,16]. Interestingly, no consensus exists regarding the influence that this has on the operating time [15][16][17][18]. The complexity of the dissection as it relates to the increased vascularity and vasoactive characteristics of PHE may contribute to this inconsistency.…”
Section: Discussionmentioning
confidence: 87%
“…In contrast to other adrenal tumors, pheochromocytomas present as a management challenge, due to their size, vascularity, and demanding pre-, intra-, and post-operative care, secondary to their hormonal secretion. A cancer diagnosis is also of concern, as 5–6% of pheochromocytomas are malignant (46). As a result, a diagnosis of pheochromocytoma was once considered a contraindication for laparoscopy.…”
Section: Introductionmentioning
confidence: 99%